THE RESULTS OF IMPLEMENTING PEER INSTRUCTION AS AN ACTIVE LEARNING STRATEGY - Bai Bayintala (International Journal of Innovative Technologies in Social Science, 2025)
In recent times, there has been a shift away from traditional teacher-centered teaching methods in all levels of education, particularly in universities. Students are now actively engaged in lessons, with teachers taking on a guiding role. This shift necessitates that teachers become proficient in innovative teaching techniques to enhance their effectiveness. As such, our study focused on the impact of active learning methods on students’ motivation and learning outcomes, specifically in seminar classes. The article begins by discussing the theoretical underpinnings of teaching methods and active learning approaches. The research section outlines a plan to implement a history seminar using the Peer Instruction active learning method with students in the Inner Mongolia Autonomous Region of China, followed by an analysis of the results obtained from this teaching approach.